'A seamless transition': how to sustain a community health worker scheme within the health system of Gombe state, northeast Nigeria. Issue 7 (15th June 2021) - Wickremasinghe, Deepthi; Alkali Hamza, Yashua; Umar, Nasir; Willey, Barbara; Okolo, Magdalene; Gana, Ahmed; Shuaibu, Abdulrahman; Anyanti, Jennifer; Marchant, Tanya; Spicer, Neil
Abstract: Health interventions introduced as part of donor-funded projects need careful planning if they are to survive when donor funding ends. In northeast Nigeria, the Gombe State Primary Health Care Development Agency and implementing partners recognized this when introducing a Village Health Worker (VHW) Scheme in 2016. VHWs are a new cadre of community health worker, providing maternal, newborn and child health-related messages, basic healthcare and making referrals to health facilities. This paper presents a qualitative study focussing on the VHW Scheme's sustainability and, hence, contributes to the body of literature on sustaining donor-funded interventions as well as presenting lessons aimed at decision-makers seeking to introduce similar schemes in other Nigerian states and in other low- and middle-income settings. In 2017 and 2018, we conducted 37 semi-structured interviews and 23 focus group discussions with intervention stakeholders and community members. Based on respondents' accounts, six key actions emerged as essential in promoting the VHW Scheme's sustainability: government ownership and transition of responsibilities, adapting the scheme for sustainability, motivating VHWs, institutionalizing the scheme within the health system, managing financial uncertainties and fostering community ownership and acceptance. Our study suggests that for a community health worker intervention to be sustainable, reflection and adaption, government and community ownership and a phased transition of responsibilities are crucial.